A study to assess biochemical profile of tobacco chewers with chewing habit over a period of 10 years - Navdeep Singh Kathuria; Sandeep Kumar Patel; Manjinder Kaur; Rohin Garg; Aryan Sidhu; Parveen Sharma (Wolters Kluwer Medknow Publications, 2024)
The study was conducted to evaluate the systemic adverse effects of smokeless tobacco (SLT) on hematological as well as other biochemical parameters and find out if any correlation between them which may be worthy of creating awareness among the masses against its usage. The current observational study was carried out among 250 tobacco chewers, and complete hemogram, LFT profile, and electrolyte profile were studied. The mean values of hemoglobin (Hb) gram % was 12.74 ± 1.6, total leucocyte count (TLC/cu mm) is 6608.33 ± 1752.083, and platelet count lakh cell/cu mm is 2.55 ±0.806. The mean values of Na+ mmol/1 of the S. electrolyte profile was 132 ± 18.05 and K+ mmol/1 was 3.89 ± 0.538. The study deliberates imperative perception into smokeless tobacco-mediated effects on body systemic functions and reports a crucial part into SLT-mediated effects on biochemical profile and metabolism which can be revealed in promoting tobacco cessation.